Subchronic preexposure to carbon monoxide modifies heart response to a combined CO + isoproterenol challenge in rats - Trávníčková, Zdeňka; Frantík, Emil; Blazek, K; Janoušek, Stanislav (General physiology and biophysics, 1999)
The effect of repeated exposure to carbon monoxide (CO) on the response of middle-age rats to an acute CO exposure combined with a low dose of a sympathomimetic agent was studied. A group of 12 rats (male albino, Wistar, age 9 months) without ECG abnormalities was divided into two subgroups matched for weight, heart rate and ECG: one subgroup was exposed to 500 ppm CO for 6 h/d, 5 d/w, for 6 weeks (peak COHb 31.5%, SD 3.5); the other one (controls) was exposed to fresh air. Two or three days after the last exposure both groups underwent combined challenge with 0.025 mg/kg isoproterenol s.c. and 90 minute exposure to CO in a concentration increasing from 500 to 1500 ppm; ECG was recorded continuously. The hearts were examined morphometrically and histologically. The CO-preexposed subgroup had, as compared to controls: 1) significantly higher blood hemoglobin (by 25%), erythrocyte count (by 28%) and volume (by 6%), and hematocrit (by 33%); 2) the same peak COHb; 3) lower basic heart rate and an earlier decrease after isoproterenol, 4) significantly smaller increase in ECG abnormalities and arrhythmias after isoproterenol and during CO exposure; 5) nonsignificantly higher heart weight indexes; 6) a nonsignificantly lower score of histological abnormalities. The global score of ECG pathology during CO exposure (abnormal pattern or arrhythmia) correlated best (multiple corr. coef. >0.9) with end-exposure free (non CO bound) hemoglobin (negatively) and with mean heart rate during exposure (positively): the lower score in the preexposed subgroup was attributable primarily to the increased hemoglobin. Six-week intermittent CO exposure induced marked compensatory processes (hematological) but only a tendency to adaptational changes in the heart (by gross morphometry), and decreased the ECG response to CO+ isoproterenol challenge at the same COHb.
Keywords: počet erytrocytů; Carbon Monoxide; objem erytrocytu; Hemoglobins; Electrocardiography; Isoproterenol; Male; Hematocrit; Rats, Wistar; lékové interakce; srdce; Heart Rate; hematokrit; mužské pohlaví; srdeční arytmie; srdeční frekvence; potkani Wistar; hemoglobiny; Arrhythmias, Cardiac; Erythrocyte Volume; krysa rodu Rattus; Animals; Erythrocyte Count; Drug Interactions; zvířata; Rats; isoprenalin; Heart; oxid uhelnatý; elektrokardiografie